Profil Keterampilan Membangkitkan Motivasi Belajar Siswa Sekolah Menengah Atas di Palembang - Sava Salsabila; Nyayu Fatimah Azzahra; Nanda Qanita; Sony Khoirilsyah; Silvia AR; Khadijah Lubis (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to describe the profile of students' skills in arousing learning motivation among senior high school students, especially at IT Izzuddin High School Palembang. This research was conducted on grade 11 students totaling 21 people. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and questionnaires. The results showed that the 11th grade students of Izzuddin High School Palembang had diverse learning motivation with the acquisition of 10 people in the low category, 8 people in the medium category, and 3 people in the high category. This data was generated from the analysis of a questionnaire filled out by 21 students, which measured various aspects of learning motivation, including the desire to learn, future hopes and aspirations, rewards in learning, a comfortable and conducive learning environment and learning strategies used. Factors that influence learning motivation were identified as teacher support, a conducive learning environment and parental involvement. This study suggests training and skill development programs for students to further enhance their learning motivation.